GABA(B) receptor activation ameliorates spatial memory impairments in stress-exposed rats - Sahraei, Hedayat (Neuropsychiatr Dis Treat, 2019)
Objective: Due to the prevalence of stress in modern life and its impact on spatial memory, the role of inhibitory systems in brain areas such as the nucleus accumbens (NAc) in reducing stress is important. The current study aimed to examine the response of NAc shell GABA(B) receptors to stress and the role of intraperitoneally (i.p.) and intra-NAc injection of the GABA(B) receptor agonist baclofen on spatial memory impairments in stress-exposed rats. Methods: Eighty adult male Wistar rats were randomly divided into ten groups (n=8): two were control groups for intra-NAc and i.p baclofen; two groups were subjected to stress and injected with saline (baclofen vehicle); three groups were given baclofen (1, 5, and 10 µg/rat) intra-NAc 5 mins before stress was induced; and three groups received baclofen (1, 5, and 10 mg/kg/i.p.) 30 mins before being subjected to stress. Foot-shock stress was applied for 7 consecutive days. Behavioral assays using the Barnes maze were performed 24 hrs after the last baclofen injection. Results: Both the intra-NAc and the i.p administration of baclofen dose-dependently reduced escape latency and total distance and increased velocity in the treatment groups in the training trials. In the probe test, the rats that had received 5 mg/kg of baclofen had the highest target frequency, but there no significant differences were observed in velocity, duration, or distance to the target between the groups. Conclusion: According to the findings, baclofen can dose-dependently improve spatial memory, and GABA(B) receptor in the NAc plays an important role in spatial memory.